406 CDX527–01, a phase 1 dose-escalation and expansion study of the PD-L1xCD27 bispecific antibody CDX-527 in patients with advanced malignancies. (9th November 2020) - Yellin, Michael; Rawls, Tracey; Young, Diane; Golden, Philip; Vitale, Laura; He, Li-Zhen; Thomas, Lawrence; Keler, Tibor
Abstract : Background: CD27 ligation and PD-1 blockade elicit complementary signals mediating T cell activation and effector function. CD27 is constitutively expressed on most mature T cells and the interaction with its ligand, CD70, plays key roles in T cell costimulation leading to activation, proliferation, enhanced survival, maturation of effector capacity, and memory. The PD-1/PD-L1 pathway plays key roles in inhibiting T cell responses. Pre-clinical studies demonstrate synergy in T cell activation and anti-tumor activity when combining a CD27 agonist antibody with PD-(L)1 blockade, and clinical studies have confirmed the feasibility of this combination by demonstrating safety and biological and clinical activity. CDX-527 is a novel human bispecific antibody containing a neutralizing, high affinity IgG1k PD-L1 mAb (9H9) and the single chain Fv fragment (scFv) of an agonist anti-CD27 mAb (2B3) genetically attached to the C-terminus of each heavy chain, thereby making CDX-527 bivalent for each target. Pre-clinical studies have demonstrated enhanced T cell activation by CDX-527 and anti-tumor activity of a surrogate bispecific compared to individual mAb combinations, and together with the IND-enabling studies support the advancement of CDX-527 into the clinic. Methods: A Phase 1 first-in-human, open-label, non-randomized, multi-center, dose-escalation and expansion study evaluating safety, pharmacokinetics (PK), pharmacodynamics (PD), and clinical activity of CDX-527 is ongoing. Eligible patients have advanced solid tumor malignancies and have progressed on standard-of-care therapy. Patients must have no more than one prior anti-PD-1/L1 for tumor types which have anti-PD-1/L1 approved for that indication and no prior anti-PD-1/L1 for tumor types that do not have anti-PD-1/L1 approved for that indication. CDX-527 is administered intravenously once every two weeks with doses ranging from 0.03 mg/kg up to 10.0 mg/kg or until the maximum tolerated dose. The dose-escalation phase initiates with a single patient enrolled in cohort 1. In the absence of a dose limiting toxicity or any ≥ grade 2 treatment related AE, cohort 2 will enroll in a similar manner as cohort 1. Subsequent dose-escalation cohorts will be conducted in 3+3 manner. In the tumor-specific expansion phase, up to 4 individual expansion cohort(s) of patients with specific solid tumors of interest may be enrolled to further characterize the safety, PK, PD, and efficacy of CDX 527. Tumor assessments will be performed every 8-weeks by the investigator in accordance with iRECIST. Biomarker assessments will include characterizing the effects on peripheral blood immune cells and cytokines, and for the expansion cohorts, the impact of CDX-527 on the tumor microenvironment. Results: N/A Conclusions: N/A Trial Registration: NCT04440943 Ethics Approval: The study was approved by WIRB for Northside Hospital, approval number 20201542